Pelatihan Pembuatan Nano Liquid Aromaterapi bagi Kader PKK Desa Wajok Hilir di Kabupaten Mempawah: Training on Manufacturing Aromatherapy Nano liquid for PKK Cadres in Wajok Hilir Village in Mempawah District - Pratiwi, Liza; Wijianto, Bambang; Fahrurroji, Andhi; Yuswar, Muhammad Akib (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
So far, essential oils have only been used as perfume and sold as raw material. On average, residents of Wajok Hilir village have yards covered with essential oil-producing plants such as lavender, lemongrass, and coconut. The aim of the PKM Program is training in utilizing community resources to make essential oils for aromatherapy in nano-liquid preparations. The development of this product must be oriented towards developing a practice that is easy to apply and environmentally friendly without ignoring environmental health. The solution to overcome existing problems is to provide knowledge to partners about the benefits of nano liquid preparations as aromatherapy and mosquito repellent and training on using essential oils as aromatherapy. Pharmacists provided training on making